BIOSIGNAL AND MEDICAL IMAGE ANALYSIS FOR HEALTH MONITORING - Than, Joel Chia Ming, 1989-, contributor; Norliza Mohd. Noor, contributor; Siti Armiza Mohd. Aris, contributor; Siti Zura A. Jalil @ Zainuddin, contributor; Amran Hussin, contributor; Cvetkovis, Dean; Hossein Ebrahimian, contributor; Mohd. Nasir Taib, contributor; Omar Mohd. Rijal, contributor; Haslaile Abdullah, editor; Norliza Mohd. Noor, editor; Hannah Sofian, contributor; et al. (Johor Bahru, Johor : Penerbit UTM Press, 2017)
Includes bibliographical references and index :p.120